British Romanticism in European Perspective
XI, 286 p.
Keywords: What, and when, is British Romanticism, if seen not in island isolation but cosmopolitan integration with European Romantic literature, history and culture? The essays here range from poetry and the novel to science writing, philosophy, visual art, opera and melodrama; from France and Germany to Italy and Bosnia.